1985
DOI: 10.1159/000249501
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Abnormalities Occurring with Alopecia areata

Abstract: This study was carried out on 83 patients with alopecia areata. Ophthalmological examinations showed lens changes in 65 patients and alterations in the retinal epithelium in 28 patients. The relationships between pigment cells and hair cycle are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 7 publications
2
51
0
Order By: Relevance
“…In our study we found that lenticular opacities were found in 35.3% cases as compared to 5.8% in controls (p<0.005).Similar observations have been reported by Recupero et al [7] and Tosti [6] et al who found lenticular changes in 78% and 51% cases of alopecia areata as compared to 27% and 3% in control groups respectively while Summerly et al [8] and Bianchi et al [9] did not found any statistically significant association of lenticular opacities in alopecia areata cases versus controls. Pandhi et al [10] on examining 83 AA patients found that 20 patients had punctate opacities, 6 and 4 patients had posterior and anterior subcapsular cataract respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study we found that lenticular opacities were found in 35.3% cases as compared to 5.8% in controls (p<0.005).Similar observations have been reported by Recupero et al [7] and Tosti [6] et al who found lenticular changes in 78% and 51% cases of alopecia areata as compared to 27% and 3% in control groups respectively while Summerly et al [8] and Bianchi et al [9] did not found any statistically significant association of lenticular opacities in alopecia areata cases versus controls. Pandhi et al [10] on examining 83 AA patients found that 20 patients had punctate opacities, 6 and 4 patients had posterior and anterior subcapsular cataract respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have been done reporting ocular findings in AA patients where lenticular and retinal abnormalities have been documented [5], [6]. Relatively there is paucity of studies reporting tear film changes and ocular surface pathologies in AA patients in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…While AA is not life threatening, the psychological impact of sudden and extensive hair loss can have significant quality of life repercussions for those affected [5]. Individuals with AA are more susceptible to developing other autoimmune diseases, particularly hypothyroidism [6], commonly have associated nail defects [7], and may also have an increased frequency of eye defects [8].…”
Section: Introductionmentioning
confidence: 99%
“…It most commonly presents with patchy areas of hair loss on the scalp and other body parts (so-called patchy AA), but can progress to loss of all scalp hair (A. totalis) and complete loss of all body hair (A. universalis). However, AA remains a highly heterogeneous systemic disease characterized by frequent involvement of other melanocyte-containing tissues, including the nails and eyes [105,106], again suggesting that the defect may be extrinsic to the HF. AA is associated with a number of immune abnormalities [107], some nonselective, while others are more specific and point to an immune abnormality selectively targeting or reacting to a component of the HF when in the anagen phase of the hair-growth cycle [108].…”
Section: New Diagnostic Techniques and Preventative Strategiesmentioning
confidence: 99%